2022
DOI: 10.3390/s22197316
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefit of Structural Health Monitoring System on Civil Jet Aircraft

Abstract: Structural health monitoring represents an interesting enabling technology towards increasing aviation safety and reducing operating costs by unlocking novel maintenance approaches and procedures. However, the benefits of such a technology are limited to maintenance costs reductions by cutting or even eliminating some maintenance scheduled checks. The key limitation to move a step further in exploiting structural health monitoring technology is represented by the regulation imposed in sizing aircraft composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…As the tables show, it is clear that the edge detection principle at the base of the methodology is able to detect the damage onsets (Figures 23 and 24). It is also important to remark that numerical studies have demonstrated that the effect of the damage over the strain field extends larger than the current damage size [20]; therefore, it can be expected to find out readouts at the inner and outer boundaries of the damage borders.…”
Section: Shm Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As the tables show, it is clear that the edge detection principle at the base of the methodology is able to detect the damage onsets (Figures 23 and 24). It is also important to remark that numerical studies have demonstrated that the effect of the damage over the strain field extends larger than the current damage size [20]; therefore, it can be expected to find out readouts at the inner and outer boundaries of the damage borders.…”
Section: Shm Resultsmentioning
confidence: 97%
“…Hence, in the absence of a jump/edge, the cumulative damage index (2) will be small. On the contrary, if an edge is present, then the two function values in (2) will be quite different from zero [20].…”
Section: Test Preparation and Test Article Description Including The ...mentioning
confidence: 97%
See 1 more Smart Citation
“…PdM techniques encourage non-damaging testing methods such as acoustic, infrared, sound level, oil analysis, vibration analysis and thermal image recognition that measure and collect real-time data of equipment through sensors. Classification of sensor data with the aid of AI or statistical techniques is the most basic building block of PdM activities in order to estimate time of the failure or RUL of the equipment [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%